Effects of Native Vacancies on Nb-Doped MgH 2 Using Density Functional Theory Calculations - Gaztañaga, Francisco (2018)
In the present work, we considered the effect of Nb and charged vacancies on the properties of magnesium hydride. We performed spin-polarized ab initio calculations substituting an Mg atom by an Nb impurity. Then, some charged vacancies were included in the MgH 2 + Nb system (V H , V Mg , or V Mg-H ). In each case, three possible charge states were considered (+1, 0, or -1). We computed cohesion and formation energies, band gap, and magnetic moment. We also calculated the transition level energy value and the density of states. Nb states are located in the gap, and a magnetic moment is induced. In the case of the system with charged vacancies, we found that V H + and V H 0 are the more probable vacancies formed, and the states near the Fermi level (E F ) are filled, thus getting an important reduction in the band gap.